Focus Position for Stripping Remnant - Mohammad Ali Al Zahrani; Khulud Helal Al Thagafi (JURNAL ARBITRER, 2020)
The current paper examines the syntactic properties of HA stripping: a type of ellipsis. Within the Minimalist framework, the paper adopts the PF-Deletion approach to show that stripping in HA is derived firstly by the movement of the remnant constituent from TP to Focus Position (FP), and, secondly, by the deletion of the TP. These two operations are licensed by the Ellipsis feature (E) located in the focus head FÂ°. Thus, on the one hand, the paper contributes to the existing body of literature supporting the hotly-debated issues on the movement of the stripping remnants, and on the other, enriches the very minimal HA studies on ellipsis. The findings show that HA stripped constituents must move to Spec, FP, before the TP- deletion process. Two pieces of evidence in support of the focus movement to FP spring from Island sensitivity and p-stranding facts in HA.